IMPLEMENTASI KEBIJAKAN UNDANG-UNDANG NOMOR 34 TAHUN 2004 DALAM OPTIMALISASI KOORDINATIF PERAN INSPEKTORAT KODAM VII/WIRABUANA UNTUK MENINGKATKAN PELAKSANAAN TUGAS POKOK KODIM 1306/DONGGALA - Alam, Sainul (Katalogis, 2013)
The research was aimed at analizing the Policy Implementation of Article Number 34/2004 in optimizing coordinative role of Kodam VII/Wirabuana Inspectorate to improve the main job realazation of Kodim 1306/Donggala. The method of the research was qualitative research. The number of informan was five people, who were chosen based on purposive sampling. The techniques of data collection which were used included observation, interview and documentation. Based on the analysis, the policy implementation of Article Number 34/2004 in optimizing coordinative role of Kodam VII/Wirabuana Inspectorate to improve the main job realization of kodim 1306/Donggala ran quite well. From the six indicators, only one dimension which ran less well, that was on the dimension of human resources; while other dimensions like policy standard and goal, executor organization characteristic, executors attitude, communication inter organization, and social, economical and political environment.